Computational modeling of acetic acid and water separation through a hybrid pervaporation-distillation process - Jelita Bungin (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Separation of acetic acid and water mixture is energy intensive and expensive due to small difference in boiling point. Conventional method of distillation thus required large numbers of trays and a high reflux ratio to obtain glacial acetic acid. In this project, a hybrid separation process combining distillation and pervaporation is proposed to explore whether an economic improvement can be established. Simulation was done using HYSYS flow sheeting while Matlab Graphical User Interface (GUI) was used to model the pervaporation unit. The total energy used in standalone distillation column is compared with the total energy used in the hybrid process. GUI of membrane pervaporation was successfully designed in the Matlab, however the design and calculation was standalone and is not integrated into the HYSYS. The results for stand-alone distillation showed that the process needs 6313 kJ/h of heat to distill 0.6594 wt of water in the top product while the energy used for pervaporation unit is dependent on the type and membrane configurations. Evaluation of a hybrid process showed that it may use less energy than a standalone distillation process by optimizing the membrane configurations. In conclusion, the modeling of acetic acid and water separation through a hybrid pervaporation-distillation process was only partially achieved due to the difficulty in integrating the GUI of the pervaporation unit into HYSYS.